COMPOSITION OF ELECTORAL AUTHORITIES AND ITS POLITICAL SIGNIFICANCE FOR ELECTORAL GOVERNANCE - Nikolai Vladimirovich Grishin (Современная наука и инновации)
The composition of the electoral management bodies has been studied by domestic scholars within the administrative law context. Less attention has been paid to the political consequences of models of electoral authorities' composition. The article examines the political significance of the different approaches to the formation of electoral management bodies. For the first time we investigate the problem of the diversity of models of participation of the various authorities and branches of power in the appointment of members of the electoral management bodies. We suggest a typology of models of the appointment of members of electoral authorities. We characterize the forms of participation of political parties' representatives in election commissions. Author rightly points the question of the status of members of the electoral authorities. his paper challenges conclusions about the political importance of the various models of formation of electoral bodies.